2007
DOI: 10.1210/jc.2007-0091
|View full text |Cite
|
Sign up to set email alerts
|

Raised Serum, Adipocyte, and Adipose Tissue Retinol-Binding Protein 4 in Overweight Women with Polycystic Ovary Syndrome: Effects of Gonadal and Adrenal Steroids

Abstract: Context: Polycystic ovary syndrome (PCOS) is associated with insulin resistance and obesity. Recent studies have shown that serum retinol-binding protein 4 (RBP4) levels increase with obesity. Currently, no data exist on the relative expression of RBP4 in either serum or adipose tissue of PCOS women.Objectives: mRNA expression of RBP4 from sc and omental (om) adipose tissue and sc adipocytes in overweight PCOS women were compared with matched controls; RBP4 protein in adipose tissue and serum RBP4 levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 21 publications
7
79
2
Order By: Relevance
“…Although PCOS is an insulinresistant state, PCOS per se and insulin resistance do not seem to be related to high RBP4 levels. We did not demonstrate a correlation between serum RBP4 levels and markers of insulin resistance in overweight women with PCOS at baseline, confirming previous observational PCOS studies (7,15). Other than that of Graham et al (4), most studies in weight-matched diabetic and obese subjects have not demonstrated a relationship with RBP4 and insulin resistance (5,6,8,10).…”
Section: Correlations With Change In Rbp4supporting
confidence: 78%
See 1 more Smart Citation
“…Although PCOS is an insulinresistant state, PCOS per se and insulin resistance do not seem to be related to high RBP4 levels. We did not demonstrate a correlation between serum RBP4 levels and markers of insulin resistance in overweight women with PCOS at baseline, confirming previous observational PCOS studies (7,15). Other than that of Graham et al (4), most studies in weight-matched diabetic and obese subjects have not demonstrated a relationship with RBP4 and insulin resistance (5,6,8,10).…”
Section: Correlations With Change In Rbp4supporting
confidence: 78%
“…In contrast, human data are equivocal, with high adipocyte and plasma RBP4 levels being reported inconsistently in insulin-resistant states, including obesity, IGT, type 2 diabetes, and PCOS (3)(4)(5)(6)(7)(8)(9). Relationships of RBP4 with features of the metabolic syndrome have also been inconsistently demonstrated (4,6,8).…”
mentioning
confidence: 99%
“…RBP4 may not be a 'common denominator' of all forms of insulin resistance. RBP4 can be affected by alterations of sex hormones, as evidenced by the fact that 17β-oestradiol can increase RBP4 mRNA expression and RBP4 secretion from human adipose tissue and women with polycystic ovary syndrome have elevated adipose tissue and serum RBP4 levels [40]. Furthermore, progesterone in the presence of oestradiol decreases RBP4 content in the female reproductive tract [41].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Yildizhan et al (2011) reported significantly higher RBP4 and homeostatic model assessment (HOMA) index in obese PCOS women as compared with nonobese PCOS and control groups. Tan et al (2007) investigated the expression of RBP4 in SC and OM adipose tissue in overweight women with PCOS and weight-matched controls, and assessed the effects of sex steroids on RBP4 expression in SC and OM fat explants. RBP4 protein levels were significantly higher in PCOS SC and OM adipose tissue.…”
Section: Visfatinmentioning
confidence: 99%